2015
DOI: 10.17675/2305-6894-2015-4-1-075-084
|View full text |Cite
|
Sign up to set email alerts
|

Performance of phosphonates as copper(II) ions stabilization agents for industrial water systems

Abstract: Copper(II) salts have long been used to kill algae in water systems, but they can precipitate as insoluble salts and form deposits on equipment surface. It is important to remove toxic metal from industrial waste because of contamination and toxicity issues. This paper discusses the testing and effects of various phosphonates to control copper-based fouling in the industrial water systems. It has been found that Cu(II) ions stabilization (complexation, precipitation, dispersion, etc.) strongly depends on solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Results of these studies show that CMI polymers exhibit poor performance compared to synthetic polymers. Amjad [17], in another study on the evaluation of phosphonates as Cu(II) stabilization agents showed that performance of phosphonates strongly depends on the concentration of phosphonate in solution and the phosphonate architecture.…”
Section: Introductionmentioning
confidence: 99%
“…Results of these studies show that CMI polymers exhibit poor performance compared to synthetic polymers. Amjad [17], in another study on the evaluation of phosphonates as Cu(II) stabilization agents showed that performance of phosphonates strongly depends on the concentration of phosphonate in solution and the phosphonate architecture.…”
Section: Introductionmentioning
confidence: 99%